Effect of Ultraviolet-C Light-Emitting Diode Treatment on Disinfection of Norovirus in Processing Water for Reuse of Brine Water - Yoon, So-Ra; Ha, Sanghyun; Park, Boyeon; Yang, Ji-Su; Dang, Yun-Mi; Ha, Ji-Hyoung (Frontiers in Microbiology, 2022)
Processes in the food industry that use large amounts of water have been an important cause of waterborne disease outbreaks, as they expose individuals to risks for waterborne disease transmission. Developing technologies to ensure the hygiene and safety of food-processing steps is an urgent concern from an economic perspective. Among the major manufacturing processes in the kimchi industry, the brining process for salted kimchi cabbages requires a considerable amount of brine (approximately 2,000–2,500 L/1,000 kg). The aim of this study was to establish virucidal conditions with ultraviolet-C light-emitting diodes (UVC LEDs) that can ensure the microbiological safety of brine water samples with various turbidities for reuse after disinfection. For quantitative analysis, first of all, magnetic bead separation (MBS) technique was used to capture and recover the human norovirus (HuNoV) virus particles; propidium monoazide (PMA) combined with RT-qPCR (PMA-RT-qPCR) was subsequently used to selectively detect infectious norovirus. Overall, as the turbidity of the brine water samples increased, the reduction in the HuNoV genogroup II genotype 4 (HuNoV GII.4) levels by UVC LED disinfection decreased. The derived inactivation rate constant (kinac) and inactivation curves (calculated using the log-linear model) were studied as a function of turbidity based on the exponential one-phase inactivation kinetics of HuNoV. Using an impeller system set at 100 rotations/min (rpm) with an eight-nephelometric turbidity unit (NTU) sample (the lowest turbidity studied), the kinact based on the levels of viral genomic RNA concentrations was approximately 2.15-fold higher than that observed without rotation (0 rpm). Moreover, the kinact increased 1.69-fold with a 56-NTU sample (the highest turbidity studied) when the impeller system was set at 100 rpm. UVC LED treatment decreased the HuNoV GII.4 population more effectively in conjunction with the impeller system (100 rpm) than without the impeller system. Our novel findings and model provide fundamental and scientific data that may help reuse brine water and ensure its microbiological safety through disinfection. Our study highlights the benefits of UVC LED treatment in successfully eliminating waterborne viruses in a prompt, resistance-reducing, and energy-efficient approach at the laboratory scale, which lays the foundation for future plant-scale studies of UVC LED-disinfection systems.